The Cyprus Problem Since the December 1999 EU Decisions at Helsinki - Coufoudakis, Van (Études helléniques / Hellenic Studies, 2000)
This article focuses on developments in the Cyprus problem since the December 1999 European Union Helsinki decisions which affected Turkey’s European orientation and confirmed Cypruspath to membership. While these positive developments were taking place, the United States, supported by the United Kingdom, also undertook major diplomatic initiatives under the mantle of the United Nations in order to resolve the Cyprus problem. However, these initiatives undermined both the credibility of the United Nations and the application of the acquis in the case of Cyprus. Hence the Cyprus problem has now come to its most critical point since the 1974 Turkish invasion of the island republic.